Analisis Hukum Normatif terhadap Kedudukan Jaksa sebagai Dominus Litis dalam Sistem Peradilan Pidana - Hanyfa Rahesti Lerian; Nadhifa Yolanda Rachmat; Zhabilla Eka Arindra Putri; Siti Sholekhah; Mawar Dwi Wahyu Sejati; FX. Hastowo Broto Laksito (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
This study aims to analyze the position of the public prosecutor as dominus litis within the Indonesian criminal justice system and to examine its implications for the principles of legal certainty, justice, and legal utility. The concept of dominus litis places the public prosecutor as the controller of criminal cases, possessing the authority to determine the continuation of the prosecution process. Therefore, the prosecutor plays a crucial role in establishing an effective and fair criminal justice system. This research employs a normative legal research method using both a statutory approach and a conceptual approach. The data consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively through a library research method. The study focuses on the regulation of prosecutorial authority as stipulated in Law Number 11 of 2021 concerning the Public Prosecution Service of the Republic of Indonesia, the Indonesian Criminal Procedure Code, and various relevant legal doctrines and theories. The findings reveal that the legal framework governing the position of the public prosecutor as dominus litis has not been explicitly and comprehensively formulated in statutory regulations. As a result, the prosecutor's authority as the controller of criminal cases remains partial and has not been implemented optimally. This condition affects the realization of legal certainty, creates the potential for injustice due to uncontrolled discretion, and limits the achievement of legal utility in criminal justice practice. Therefore, a more comprehensive, integrated, and reform-oriented legal framework is required to strengthen the prosecutor's authority as dominus litis in order to support the development of an effective, fair, and legally certain criminal justice system.